In the Clearing - Hardy, Billy (Murmurations: Journal of Transformative Systemic Practice, 2023)
Some context I brought these words together in 2022 following a weekend I spent with my younger sister, Annemarie, and my younger brother, James, who came to visit me together, something that hadn’t happened before and I was left humbled by their visit. The conversations we created as the remaining elder generation of our family were moving and it was the first time such conversations took place. The context for this coming together was triggered by a chemotherapy treatment phase following my recent diagnosis of cancer. This weekend became an important event in our lives thus far, and as I was exploring poetry as an antidote to patient-hood, as well as making my voice find its relationship to myself inhabited by cancer, I try to capture our conversations and share them with you here. My sister and brother have given me permission to publish this. I honour them as “us” and our experiences we have shared.